Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
First, solve for y.
1/3x - 1/6y = 0
-1/3x -1/3x
-1/6y = -1/3x (divide by -1/6, you basicallt multiply by -6)
y = 2x
1/3x - 1/6y = 0
-1/3x -1/3x
-1/6y = -1/3x (divide by -1/6, you basicallt multiply by -6)
y = 2x
[tex]\frac{1}{3}x- \frac{1}{6}y=0 \\ \\\frac{1}{6}y = \frac{1}{3}x \ \ /*6 \\ \\y=\frac{1}{\not3^1}x*\not6^2 \\ \\y=2x[/tex]
![View image Lilith](https://us-static.z-dn.net/files/d66/45961b871e84665be72949dfceca3276.png)
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.